PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN BUDAYA ORGANISASI, TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN GIANYAR - Sang Ayu Setya Nusani; Nengah Landra; Ni Made Dwi Puspitawati (VALUES, 2021)
Performance is a real behavior that is generated by each employee as a performance achievement that is generated according to their role in the company. Good performance is influenced by several factors such as leadership, communication, organizational culture. This study aims to examine the influence of leadership, communication, organizational culture on employee performance at the Department of Industry and Trade, Gianyar Regency, located on Jl. Erlangga Civik Center Gianyar. Data collection was carried out through observation, interviews, questionnaires, documentation. The sample used in this study were 35 employees at the Industry and Trade Service of Gianyar Regency. This study uses multiple linear analysis methods, Classical Assumption Test, F test, T test with analysis tools, namely SPSS version 25 For Windows. The results showed that leadership has a positive effect on employee performance, communication has a positive effect on employee performance and organizational culture has a positive effect on employee performance.